Factor V H1299r (Hr2) Heterozygosity: A Risk Factor For Recurrent Implantation Failure Particularly In Non-Carriers For Factor V Leiden Mutation-A Case-Control Study - Ozgu-Erdinc, A. Seval; Gulsen Coban, Pınar; Yilmaz, Nafiye; Candemir, Zuhal; Yilmaz, Saynur; Erkaya, Salim (Gynecology Obstetrics & Reproductive Medicine, 2022)
Objective: The association between recurrent implantation failure and thrombophilia is still controversial depending on the published reports with conflicting results. In this study, we aimed to assess the clinical relevance of screening women with recurrent implantation failure for some thrombophilic variants including factor V H1299R (FV HR2) haplotype. Study Design: A total of 279 women were recruited in this case-control study. 229 women with a history of recurrent implantation failure and 50 fertile control with no history of pregnancy losses were screened for eight specific gene mutations, regarding factor V G1691A gene (FV Leiden), FV HR2, factor II prothrombin G20210A, factor XIII V34L, PAI-1 4G/5G, MTHFR C677T, MTHFR A1298C and A3 haplotype of the endothelial cell protein C receptor gene. Results: Recurrent implantation failure group displayed a significantly higher prevalence of FV HR2 heterozygosity than fertile controls while the frequency of FV Leiden mutation was comparable between groups (p=0.011; p=0.619). Additionally, the difference in the prevalence of other specific or total gene mutations among women with recurrent implantation failure was also insignificant. Discussion: The primer outcome of this study was the co-existence of the higher prevalence of FV HR2 haplotype and the insignificant percentage of FV Leiden mutation in women with recurrent implantation failure. Thus, we emphasize that the HR2 haplotype may be associated with recurrent implantation failure particularly in non-carriers for FV Leiden mutation. In the necessity of screening for thrombophilia in recurrent implantation failure, HR2 haplotype should be involved in the searched gene panel particularly in the absence of FV Leiden mutation. Further large-scale prospective studies are needed to investigate whether screening or treatment for HR2 haplotype has any detrimental impact on implantation success in cases of recurrent implantation failure.